El sandwich mas grande, jamas - Gelman, Rita Golden; Gerberg, Mort.; Vasquez, Rene. (New York : Scholastic Inc., 1987)
Un hombre con una olla viene a la partido de campo de dos ninos y hace un sandwich, lo mas grande del mundo--jamas. A strange little man with a pot on his head comes to the picnic of two children and proceeds to make a gigantic sandwich.
Translation of: The biggest sandwich ever.
Keywords: Fantasy -- Juvenile fiction; Sandwiches -- Juvenile fiction; Cooking -- Juvenile fiction